2014
DOI: 10.1002/anie.201405058
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Aerobic Oxidative Transformation of Ketone‐Derived N‐Tosyl Hydrazones: An Entry to Alkynes

Abstract: A novel strategy involving Cu-catalyzed oxidative transformation of ketone-derived hydrazone moiety to various synthetic valuable internal alkynes and diynes has been developed. This method features inexpensive metal catalyst, green oxidant, good functional group tolerance, high regioselectivity and readily available starting materials. Oxidative deprotonation reactions were carried out to form internal alkynes and symmetrical diynes. Cross-coupling reactions of hydrazones with halides and terminal alkynes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…4‐(Hex‐1‐yn‐1‐yl)benzonitrile (3cj): 1 H NMR (400 MHz, CDCl 3 ): δ = 7.48 (d, J = 8.4 Hz, 2H), 7.37 (d, J = 8.4 Hz, 2H), 2.35 (t, J = 6.8 Hz, 2H), 1.54–1.48 (m, 2H), 1.42–1.37(m, 2H), 0.87 (t, J = 7.6 Hz, 3H). 13 C NMR (100 MHz, CDCl 3 ): δ = 132.1, 131.9, 129.2, 118.7, 110.8, 95.7, 79.5, 30.5, 22.1, 19.2, 13.6.…”
Section: Methodsmentioning
confidence: 99%
“…4‐(Hex‐1‐yn‐1‐yl)benzonitrile (3cj): 1 H NMR (400 MHz, CDCl 3 ): δ = 7.48 (d, J = 8.4 Hz, 2H), 7.37 (d, J = 8.4 Hz, 2H), 2.35 (t, J = 6.8 Hz, 2H), 1.54–1.48 (m, 2H), 1.42–1.37(m, 2H), 0.87 (t, J = 7.6 Hz, 3H). 13 C NMR (100 MHz, CDCl 3 ): δ = 132.1, 131.9, 129.2, 118.7, 110.8, 95.7, 79.5, 30.5, 22.1, 19.2, 13.6.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the readily occurring Glaser coupling as the side‐reaction in the directed C−H alkynylations, the choice of alkynylation reagent played a critical role. On their continuous research interest for alkynes synthesis, Li group reported a versatile catalytic system comprising of dicationic iridium catalyst and electrophilic alkynylation reagent for the ortho C−H alkynylation of carbonyl compounds (Scheme ). Heterocycles including furan and oxazole, proceed smoothly in this ortho C−H alkynylation, and regioselective C4−H alkynylation of C3‐ester indoles was also realized.…”
Section: Cp*ir(iii)‐catalyzed C−h Activation For the C−c Bond Formationmentioning
confidence: 99%
“…In 2014, Jiang and co-workers reported an elegant divergent oxidative alkynylation of ketone-derived hydrazones that gave various internal alkynes and diynes in the presence of CuCl, DABCO, and DMSO at 100 °C under O 2 (1 atm) (Scheme 38). 74 The internal alkynes were generated from the direct dehydration of α-substituted N-tosylhydrazones (path a) or the cross-coupling reaction of methyl ketone derived N-tosylhydrazones (path b1). The alkyne-coordinated copper intermediates T43 generated in situ (R 2 = H) go through a cross-coupling or homocoupling reaction to deliver the corresponding conjugated diynes via paths b2 and b3, respectively.…”
Section: Scheme 37 Synthesis Of Vinyl Sulfones From N-tosylhydrazonesmentioning
confidence: 99%